Secure and efficient hand-over authentication in WLAN using elliptic curve RSA. (November 2017) - Krishnamoorthy, Murugan; Perumal, Varalakshmi
Abstract: Roaming of mobile nodes among multiple access points should be secure and efficient. Hand-over occurs when a mobile node migrates from one access point to another and establishes a new connection by terminating the previous one. However, designing an appropriate hand-over authentication protocol is a complex task because the processing efficiency and power of mobile node is restricted to a certain extent. The lesser security level and higher computation complexity are the main issues of the existing hand-off authentication protocols. To overcome these problems, Elliptic Curve RSA is proposed with modification in the initialization and authentication phases of the hand-off authentication protocol. The result of the proposed work shows the improvement in higher security level along with lesser computational cost. Further, the proposed algorithm is performing well against the various possible attacks.